INTERNATIONAL HUMAN RIGHTS PROTECTION: CHALLENGES TO STATE’S SOVEREIGNTY IN A DEMOCRATIC ERA - Aqimuddin, Eka An (UI Scholars Hub, 2013)
Human right violations are difficult to put to an end since in many cases the state itself is the one violating their citizen’s rights. At this point, the international community cannot intervene due to the state’s sovereignty principle. State’s sovereignty principle is one of the international laws primary principles. However, in terms of human right protections, the state’s sovereignty principle usually hinders international communities from giving their assistance in which could be seen as an intervention to the state’s sovereignty. Intervention in order to protect human rights if conducted within certain boundaries is in accordance with the UN charter provisions. Nonetheless, decision-making indecisiveness within the UN causes failure to protect the human rights. Therefore, the state’s sovereignty principle as a concept should be reviewed. Furthermore, reform is necessary at the institutional level of the UN so that dilatory decision-making can be avoided.